Incidencia de la NIC 41 Agricultura en los estados financieros de la empresa Molino La Perla S.A.C., periodo 2016, Trujillo - Zavaleta Sánchez, Yesenia del Pilar (2019)
The goal of the current investigation was to determinate how the International Accounting Standard N° 41 – Agriculture incided positive on Financial Statements of the Company Molino la Perla S.A.C. For this, the quantitative research method was used, under a non-experimental and descriptive-correlational design. For being a research focus on a concrete reality, it was taken as a study unit, population and sample of 12 people linked to the management, analysis and administration of the Financial Statements such as the accounting personnel of the Company Molino La Perla SAC, whose main activity is the production of chicken meat.In the development of this research, the interview was used as an information gathering technique, which was directed to the General Accountant and surveys to the staff of this area, likewise the State of Financial Position, the Income Statement of the entity and accounting for biological assets owned by the company were analyzed.Through the results obtained, the correlation coefficient between International Accounting Standard N ° 41 - Agriculture and the Financial Statements of the company Molino La Perla S.A.C. was 0.79, this value represents a positive and significant correlation because the confidentiality value oscillates between 0 and 1. The closer it is to 1, the more consistent the variables will be with each other.